Damage monitoring in fracture mechanics by evaluation of the heat dissipated in the cyclic plastic zone ahead of the crack tip with thermal measurements. (August 2017) - Palumbo, D.; De Finis, R.; Ancona, F.; Galietti, U.
Highlights: Evaluation of the heat dissipated at the crack tip by means of thermography. Heat dissipated varies at the twice of the loading frequency. On-line monitoring of the crack growth automatically. Abstract: Dissipated energy ahead of the crack tip represents a useful tool to study the fatigue crack growth. In this regard, different analytical and numerical models were proposed in literature to investigate the role of dissipated energy in fracture mechanics and experimental techniques were used to validate them. The experimental measurement of dissipated energy requires an accurate equipment and suitable techniques that may restrict the applications only to laboratory tests. In this work, an experimental approach by using the thermographic technique has been used to assess the heat dissipated at the crack tip in the cyclic plastic zone. The proposed approach is based on the evaluation of the heat source that occurs at the twice of the loading frequency directly related to the plastic phenomena around the crack tip. This index showed to be more suitable for on field measurement. By monitoring the fatigue crack growth during a fracture mechanics test carried out on the martensitic steel AISI 422, a similar Paris Law model was obtained between the crack growth and the heat dissipated per cycle. Moreover, it was obtained a fourth power dependence of heat dissipated energy and Stress Intensity Factor (SIF) in agreement with numerical and analytical models present in literature.